SUBALTERN THEORY AND THE ORGANIZATIONAL STRUCTURE OF THE NATIONAL COUNCIL OF WOMEN SOCIETIES, NCWS – NIGERIA - OBIJAJU, Ebele Jacinta (Socialscientia: Journal of Social Sciences and Humanities, 2020)
This study interrogates how the organizational structure of the National Council of Women Societies (NCWS)-Nigeria is interfacing with the activities of women in Nigeria taking the subaltern theory as a form of departure. Though the NCWS-Nigeria was created in 1958 to address issues of women empowerment, there is need for stocktaking vis-à-vis the high level of illiteracy, low participation in politics and decline in work force amidst cultural and religious barriers. Thus the study examines the structure of NCWS-Nigeria as an umbrella body in empowering women in Nigeria, and accordingly hypothesizes that the umbrella character of NCWS-Nigeria has significant effect on subaltern practice and the operations of the society in Nigeria. Anchored in the Radical Feminist Theory, data for the study were generated through documentary instrument and interview, and analysed using charts and analytical inductive technique. The findings reveal that the various structures instituted by NCWS-Nigeria in a bid to reach out to Nigerian women for empowerment through their organized structures could not tackle the increased challenges to women empowerment traceable to economic dependency of women on men which has its major expression in cultural practices against women created by patriarchy. Taking cognizance of these, the study recommends more openness (enlightenment programmes) from The Council so as to accommodate men and women who have genuine interest in women empowerment.